Piglets milk intake during nursing in sows treated with oxytocin - Karlsson, Elin (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2017)
Milk ejection occurs in response to release of the hormone oxytocin from the pitui-tary, and this hormone is also used as treatment of milk stasis in sows in the Swe-dish piglet production. Today, there are few reports on the effect of oxytocin injec-tion on sow milk let down, piglet and sow nursing behaviour or piglet milk intake. Therefore this study aims to investigate piglet’s milk intake in connection to oxyto-cin treatment on sows in Swedish commercial piglet producing herds. The weigh-suckle-weigh method was used to asses piglet milk intake in one nursing were the sow were treated with oxytocin, the subsequent nursing after the oxytocin treatment nursing in the same sow and one nursing in a healthy control sow. Statistical anal-yses were performed on the variables; weight of the litter, weight spread within litter, weight change during nursing, spread in weight change within litter and per-cent of weight changes of live weight. In the next step of the statistical analyses, the sows treated with oxytocin were divided into two groups; sows without udder symptom and sows with udder symptom. Due to the small size of this pilot study, only numerical differences could be found. Differences of relevance were found in the variable spread in weight change within litter between sows treated with oxyto-cin and sows without treatment. Numerical differences were observed in all of the analysed variables between sows with- and without udder symptoms indicating that intramuscular oxytocin injection have a positive effect on sows with apparent udder symptoms. The experiences from this study indicate that the weigh-suckle-weigh method is more relevant in more controlled studies in e.g. research herd, with an equal environment and there consideration about fecal, urine, metabolic or heat losses can be taken. However, under commercial conditions, recordings about sow response to the oxytocin injection can be achieved by observation of the nursing performance in connection to the injection.